2021
DOI: 10.1001/jamanetworkopen.2021.17573
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sleep and β-Amyloid Pathology Among Older Cognitively Unimpaired Adults

Abstract: IMPORTANCE Disrupted sleep commonly occurs with progressing neurodegenerative disease. Large, well-characterized neuroimaging studies of cognitively unimpaired adults are warranted to clarify the magnitude and onset of the association between sleep and emerging β-amyloid (Aβ) pathology. OBJECTIVE To evaluate the associations between daytime and nighttime sleep duration with regional Aβ pathology in older cognitively unimpaired adults. DESIGN, SETTING, AND PARTICIPANTS In this cross-sectional study, screening d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 48 publications
2
34
1
1
Order By: Relevance
“…The same group also showed that disruption of slow wave activity increases CSF amyloid beta levels acutely, and poorer sleep quality over several days increases tau levels (Ju et al, 2017). Recent large scale studies similarly report that shorter habitual sleep duration is associated with increased tau and amyloid beta levels (Insel et al, 2021;Winer et al, 2021). The glymphatic system contributes to the clearance of soluble amyloid beta as well as tau (Iliff et al, 2012(Iliff et al, , 2014Patel et al, 2019) and therefore constitutes a promising and alternative therapeutic target for curbing buildup of toxic waste protein and preventing cognitive impairment.…”
Section: Clinical Relevance Of Glymphatic Dysfunctionmentioning
confidence: 94%
“…The same group also showed that disruption of slow wave activity increases CSF amyloid beta levels acutely, and poorer sleep quality over several days increases tau levels (Ju et al, 2017). Recent large scale studies similarly report that shorter habitual sleep duration is associated with increased tau and amyloid beta levels (Insel et al, 2021;Winer et al, 2021). The glymphatic system contributes to the clearance of soluble amyloid beta as well as tau (Iliff et al, 2012(Iliff et al, , 2014Patel et al, 2019) and therefore constitutes a promising and alternative therapeutic target for curbing buildup of toxic waste protein and preventing cognitive impairment.…”
Section: Clinical Relevance Of Glymphatic Dysfunctionmentioning
confidence: 94%
“…Although the exact mechanism of sleep disturbance involved in cognitive impairment has not been fully determined. A growing number of studies have found that sleep disorders may lead to cognitive impairment and accelerate AD pathology, including increased Aβ deposition in the brain [42][43][44][45][46][47][48]. Our recent studies also showed that sleep deprivation induced peripheral Aβ transport dysfunction in young adults, and Aβ accumulation in the brain in rats [49,50].…”
Section: Discussionmentioning
confidence: 64%
“…NFT pathology was identified in 8 of 27 post-mortem TBI brains [179]. Indeed, extensive NFTs are found in up to one-third of individuals who survive a year or longer from a single TB [180]. Tau levels in TBI patients' CSF were about 1,000-fold higher than in other neurologically afflicted and non-diseased individuals [181].…”
Section: Traumatic Brain Injury [Tbi]mentioning
confidence: 99%
“…Sleeping time and (rapid eye movement) REM sleep decrease as people age. Sleep-wake cycle disruptions, such as more daytime sleep, less nocturnal sleep, and sleep fragmentation, are common in Alzheimer's disease patients[179][180]. During sleep, the interstitial space expands, facilitating Aβ clearance by increasing the exchange between CSF and ISF.…”
mentioning
confidence: 99%